The Digital Encyclopedia of Butterflies in Jatibarang Reservoir as The Supplement of Biodiversity Teaching Material in Senior High School (Universitas Negeri Semarang, 2019)
The result of observation at SMA N 2 Semarang indicates that the biodiversity teaching material has not provided information contextually that utilizes local potential. The aims of this research are to (1) examine and describe the species of butterflies in the Jatibarang Reservoir; (2) evaluate the validity of digital encyclopedia developed based on the assessment of material and media experts; (3) evaluate the effectiveness of digital encyclopedia developed in student learning outcomes; and (4) evaluate the response of students and teachers as digital encyclopedia users. This research belongs to the Research and Development study. This research is in the form of sampling and the identification of butterflies in the Jatibarang Reservoir. The development is the compilation of digital encyclopedia which is used as a material supplement. The findings of this research showed (1) the diversity of 28 butterfly species in the Jatibarang Reservoir such as Lycanidae, Nymphalidae, Papilionidae and Pieridae family; (2) the validity of the encyclopedia of butterflies according to the material and media experts in the average of 92.8 % using valid criteria; (3) the effectiveness test on cognitive aspect for N-Gain value in high category and 100% classical completeness, affective aspect for good category and psychomotor aspect for skilled category; (4) the students’ response of the digital encyclopedia are 95.9% and teachers’ response are 93.3% which belong to very good categories. The digital encyclopedia is suitable in the learning process. Hasil observasi di SMA Negeri 2 Semarang menunjukkan bahwa pembelajaran biologi materi keanekaragaman hayati belum memberikan informasi secara kontekstual yang memanfaatkan potensi lokal. Penelitian ini bertujuan (1) mengkaji dan mendeskripsikan kekayaan jenis kupu-kupu yang terdapat di Waduk Jatibarang; (2) menguji validitas ensiklopedia digital yang dikembangkan berdasarkan penilaian ahli materi dan media; (3) menguji keefektifan ensiklopedia digital yang dikembangkan dalam hasil belajar siswa; dan (4) menguji respon siswa dan guru sebagai pengguna ensiklopedia digital. Penelitian ini merupakan penelitian Research and Development. Penelitian berupa pengambilan sampel dan identifikasi kupu-kupu di Waduk Jatibarang. Pengembangan berupa penyusunan ensiklopedia digital yang kemudian dijadikan suplemen bahan ajar. Hasil penelitian menunjukkan (1) kekayaan jenis kupu-kupu di Waduk Jatibarang terdapat 28 spesies yang terdiri dari famili Lycanidae, Nymphalidae, Papilionidae dan Pieridae; (2) validitas ensiklopedia kupu-kupu dari ahli materi dan ahli media rata-rata 92,8% dengan kriteria sangat valid; (3) uji keefektifan pada aspek kognitif menujukkan nilai N-gain dalam kategori tinggi serta ketuntasan klasikal 100% tuntas, aspek afektif menunjukkan dalam kategori baik serta kategori sangat terampil untuk aspek psikomotor; dan (4) respon penggunaan ensiklopedia digital pada siswa yaitu 95,9% termasuk dalam kategori sangat baik dan respon guru mencapai 93,3% dengan kategori sangat baik. Ensiklopedia digital layak digunakan dalam proses pembelajaran.